Using images in late antiquity - Birk, Stine; Kristensen, Troels Myrup; Poulsen, Birte (Oxford : Oxbow Books, 2014)
Fifteen papers focus on the active and dynamic uses of images during the first millennium AD. They bring together an international group of scholars who situate the period's visual practices within their political, religious, and social contexts. The contributors present a diverse range of evidence, including mosaics, sculpture, and architecture from all parts of the Mediterranean, from Spain in the west to Jordan in the east. Contributions span from the depiction of individuals on funerary monuments through monumental epigraphy, Constantine's expropriation and symbolic re-use of earlier monuments, late antique collections of Classical statuary, and city personifications in mosaics to the topic of civic prosperity during the Theodosian period and dynastic representation during the Umayyad dynasty. Together they provide new insights into the central role of visual culture in the constitution of late antique societies.
1. Introduction -- 2. Chi parla a chi? Epigrafia monumentale e immagine pubblica in epoca tardoantica -- 3. Using Images for Self-Representation on Roman Sarcophagi -- 4. Maxentius, Constantine, and Hadrian: Images and the Expropriation of Imperial Identity -- 5. Late Antique Honorific Sculpture in Constantinople -- 6. Collections, Canons, and Context: The Afterlife of Greek Masterpieces in Late Antiquity -- 7. Late Antique Sculpture in Augusta Emerita and its Territory (Hispania): Officinae, Patterns and Circuits -- 8. Temples and Civic Representation in the Theodosian Period -- 9. Triumphal Arches and Gates of Piety at Constantinople, Ravenna, and Rome -- 10. Urban Armatures, Urban Vignettes: The Interpermeation of the Reality and the Ideal of the Late Antique Metropolis -- 11. City Personifications in Late Antiquity -- 12. Mythology and Theatre in the Mosaics of the Graeco-Roman East -- 13. Alla ricerca di un'identità. Tradizioni classiche nella prima iconografia Cristiana -- 14. Using and Abusing Images in Late Antiquity (and Beyond): Column Monuments as Topoi of Idolatry -- 15. The Encyclopaedic Illustration of a New Empire: Graeco-Roman-Byzantine and Sasanian Models on the Façade of Qasr al-Mshatta
Obsahuje bibliografické odkazy
Elektronická reprodukce.
Keywords: 1.-10. století; vizuální kultura -- Středozemní moře (oblast) -- 1.-10. století; vizuální komunikace -- Středozemní moře (oblast) -- 1.-10. století; vizuální umění -- Středozemní moře (oblast) -- 1.-10. století; umění a společnost -- Středozemní moře (oblast) -- 1.-10. století; starověké umění -- Středozemní moře (oblast); středověké umění -- Středozemní moře (oblast); visual culture -- Mediterranean area -- 1st-10th centuries; visual communication -- Mediterranean area -- 1st-10th centuries; visual art -- Mediterranean area -- 1st-10th centuries; art and society -- Mediterranean area -- 1st-10th centuries; ancient art -- Mediterranean area; medieval art -- Mediterranean area; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online